PENERAPAN GAYA HIDUP ZERO WASTE SEBAGAI UPAYA PENYELAMATAN LINGKUNGAN DI INDONESIA - Kartini Rustan; Andi Agustang; Idham Irwansyah Idrus (Lafadz Jaya Publisher, 2023)
Garbage in the environment is a problem that must be eradicated immediately. Waste processing cannot be separated from managing people's lifestyles. The increase in population and lifestyle of the community results in an increase in the volume of waste produced. The increasing volume of waste, which is increasing every day, has forced all parties to intervene to seek various solutions to solve this now dangerous problem. One way to reduce waste is by adopting a zero waste lifestyle, where a lifestyle that suppresses the production of waste management as optimally as possible. The research method used is library research or literature study from social media or the internet. how to implement a zero waste lifestyle with 5R namely refuse, reduce, reuse, recycle and rotting while the way to start is separating the types of waste (inorganic and organic), waste recycling, not using plastic bags when shopping, reducing paper use, using your own drinking bottles compared to buying bottled drinking water, and finally replacing using a straw.